Effect of foliar fertilizer application on yield, and yield components of tea (Camellia sinensis Var. Assamica (Mast.) Kitamura) - Haq, Muthia Syafika; Rachmiati, Yati; Karyudi, Karyudi (Jurnal Penelitian Teh dan Kina, 2014)
The experiment on the effect of foliar fertilizer (29% N, 10% P2O5, 10% K2O, 3% MgO, 5% SO3, and micro compound B, 0,0075% Cu, 0,026% Fe, 0,032% Mn and 0,023% Zn) concentration on growing tea (Camellia sinensis) and productivity was conÂducted in Research Institute for Tea and CinÂchona Experimental Plantation on the altitude of 1.350 m above sea level and Andisol type soilfrom August to November 2013 with GMB 7 clones. The experiment was arranged in a randomized block design with 3 treatments and 4 replicates. Concentration levels of fertilizer were 1) 0% as control, 2) 2%, and 3) 4%. The results showed that productivity increased significantly, control (465,25 g/10 plantation) compared with the plants were treated with 2% (564,58 g/10 plantation) and 4% (573,46 g/10 plantation) fertilizer, respectively. The increase of productivity was due to increased of plucking point, quantity and weight of pecco and length of leaves.Â